Joint Outcome of Additive Neighborhood Agregation (JOANA): método de ranqueamento para auxílio à tomada de decisão - Santos, Alex Almeida dos (Universidade do Vale do Rio dos Sinos, 2021)
In increasingly dynamic scenarios and with varieties of technology deployment projects, companies and their managers have to make more complex decisions and as assertively as possible. Currently, the literature presents approaches to methods for multicriteria decision making, however the automation and clarity of a management visualization system for these approaches is not always so clear. In addition, many works are focused on solving specific segments of companies, not seeking to cover all possible scenarios and contexts in the decision. Given this research gap, the objective of this dissertation is to propose a prioritization strategy, using the Joint Outcome of Additive Neighborhood Aggregation (JOANA) method for implementing technologies associated with Lean Office, considering two and three dimensions of analysis for decision making. In this way, this dissertation addressed topics such as Lean Office, Disruptive Technologies and Ranking methods to support decision making. In view of the practical applications and application of tools to solve a specific problem, this dissertation is classified as applied research with a quantitative approach. Using PRISMA check list as a method of systematic literature review to search for decision elements, and Design Science Research as a research method for generating and developing the research Artifact. The results obtained from the application of the method return when the method applies two dimensions a graph divided into four quadrants that classify the alternatives as Priority, Complex, Dismissable and Discussable, using as matrices concepts of effort and return, in the application of three dimensions with the added financial concept is possible to evaluate new results and three-dimensional graphic analysis, facilitating the analysis of results by managers of any level and employees. The method is based on the Order Preference Technique for Similarity to the Ideal Solution (TOPSIS), used to build matrices. An example of application of the method is presented for the ordering of practices / technologies to be implemented in a company located in the metropolitan region of Porto Alegre-RS / Brazil. The application of this matrix helped the decision maker to have a clear view of the priorities of deployments and the development of an automation artifact for the creation of new matrices allows the use of any part of the company. The research contributed to the academic environment due to using the TOPSIS method in a different way and as a visual tool for multi-criteria decision making and multidimensional, and for the business environment a tool is provided that seeks the base data and performs the transformation to the ranking method Joint Outcome of Additive Neighborhood Aggregation (JOANA).
Keywords: Priorização; Ranqueamento; TOPSIS; Lean office; Tecnologias disruptivas; Prioritization; Ranking; Disruptive technologies; ACCNPQ::Engenharias::Engenharia de Produção